Research on different structures of dimpled textures on improving the LE-FPL of engine. Issue 4 (2nd April 2021) - Wang, Peiling; Nguyen, Vanliem; Wu, Xiaoyan; Wang, Shu
Abstract : Purpose: This paper aims to research the effect of the different structures of dimpled textures on the rod bearing surfaces on improving the engine's lubrication efficiency and friction power loss (LE-FPL). Design/methodology/approach: Based on the hydrodynamic model of the rod bearing, the effect of different structures of dimpled surfaces including circular dimples (CD), square dimples (SD), wedge-shaped dimples (WSD), circular-square dimples (CSD) and square-wedge-shaped dimples (SWSD) on ameliorating the LE-FPL is analyzed under the different operating conditions of the engine. The oil film pressure ( p ), asperity contact force (Wac ), friction force (Ff ) and coefficient of friction (COF) of the rod bearing are chosen to evaluate the LE-FPL. Findings: The SD's performance on improving the LE-FPL is better than all other structures of the CD, WSD, CSD and SWSD. Particularly, the average values of Wac, Ff and COF with the SD is significantly reduced by 14.5%, 28.5% and 33.3% compared to the optimal dimensions of the rod bearing; and by 26.4%, 34.5% and 43.7% compared to the optimal CD ( n = m = 6). Originality/value: The generated friction between surfaces of rod bearings of the engine not only reduces the engine power but also affects the durability of the structures. Thus, the optimal design of the SD to further improve the LE-FPL is very necessary.